FDTD Modeling of LEMP Propagation in the Earth‐Ionosphere Waveguide With Emphasis on Realistic Representation of Lightning Source. Issue 23 (7th December 2017) - Tran, Thang H.; Baba, Yoshihiro; Somu, Vijaya B.; Rakov, Vladimir A.
Abstract: The finite difference time domain (FDTD) method in the 2‐D cylindrical coordinate system was used to compute the nearly full‐frequency‐bandwidth vertical electric field and azimuthal magnetic field waveforms produced on the ground surface by lightning return strokes. The lightning source was represented by the modified transmission‐line model with linear current decay with height, which was implemented in the FDTD computations as an appropriate vertical phased‐current‐source array. The conductivity of atmosphere was assumed to increase exponentially with height, with different conductivity profiles being used for daytime and nighttime conditions. The fields were computed at distances ranging from 50 to 500 km. Sky waves (reflections from the ionosphere) were identified in computed waveforms and used for estimation of apparent ionospheric reflection heights. It was found that our model reproduces reasonably well the daytime electric field waveforms measured at different distances and simulated (using a more sophisticated propagation model) by Qin et al. (2017). Sensitivity of model predictions to changes in the parameters of atmospheric conductivity profile, as well as influences of the lightning source characteristics (current waveshape parameters, return‐stroke speed, and channel length) and ground conductivity were examined. Key Points: Nearly full‐bandwidth FDTD model of LEMP propagation in the Earth‐ionosphere waveguide with traveling‐wave‐type source is developed Return‐stroke speed, channel length, and other model input parameters were varied to examine their influence on computed fields For independently specified source, model predictions are in reasonably good agreement with measurements, at least in daytime